Cardiac Care in Belize: Building a Local, Sustainable Program from “Square One”: Cardiac Care in Belize - Skipper, Eric; Johnson, Theresa; R, Francis (Journal of Humanitarian Cardiovascular Medicine, 2022)
Objectives: The authors explore building a sustainable cardiac program in Belize from ground zero. Methods: Leveraging previously proven experience and expertise of Francis Robicsek, MD PhD in Guatemala, the authors outline the steps taken to duplicate the program. Results: A 5-year commitment timeline between the supporting organization and the host medical facility in Belize is the first step toward achieving sustainability. We are already seeing results through advance training and hiring of healthcare providers. Conclusion: “Give a man a fish and you feed him for a day. Teach a man to fish and you feed him for a lifetime.”(1) Our role is to provide assistance and support, so that we leave competent and skilled medical professionals behind to assess, diagnose and treat current and future generations.